The Stratup: a real business simulation approach - Che Hassan, Anita; Ahmad, Junaidah Hanim; Wan Mohamad Noor, Wan Nurul Basirah; Zainal Ariffin, Muhaniza; Nik Wil, Nor Jaslina; Wan Fauzi, Wan Noor Asmuni (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Traditional Strategic Management subject primarily relies on theoretical assessments, such as business proposals and case studies, which often lack real-world applicability. To enhance experiential learning, this study introduces The StratUp: A Real Business Simulation Approach where students conceptualise, launch, and manage simulated businesses. As part of this initiative, students will design and develop a mock product representing their business idea. They will then exhibit their mock product in a business simulation exhibition, allowing them to engage with interested market, receive market feedback, and refine their strategies accordingly. This hands-on approach enhances practical learning, improves decision-making skills, fosters an entrepreneurial mindset, and bridges the gap between theory and practice. The StratUp is unique in its emphasis on execution rather than theoretical planning, continuous strategic adaptation, and students will learn to integrate their business into digital tools such as e- commerce platforms and social media marketing. Assessment extends beyond written submissions to include business execution, innovation, market response, and team collaboration. By shifting from passive to experiential learning, The StratUp equips students with essential skills to navigate complex business environments, making Strategic Management subject more dynamic, applicable, and engaging.